Impacts of Trade Unions on Employees' Welfare in UNATU, Kabale District. - Cyomperwe, Justinah (Kabale University, 2023)
The main objective of this study was to assess the impact of trade unions on employees' welfare taking the Kabale District UNA TU branch as a case study. The specific objectives were to establish the roles of trade unions on employees, to determine the challenges that face trade unions on employees' welfare and to examine the strategies that can be used to ensure effective implementation of trade unions and employees' welfare. The study specifically sought to establish the extent to which governance and leadership structures affect the performance of trade unions. A correlation research design was adopted for this study incorporating quantitative methods of data collection and the population of the study was 90 respondents consisting of members and staff of Uganda National Teachers' Union, Kabale District UNA TU branch. Data were analyzed using SPSS data analysis package version 19 which ran descriptive statistics and inferential statistics such as Pearson chi-squares to test hypotheses. The study findings revealed a positive correlation (0.789) between governance structure and Kabale District UNA TU branch's performance; a positive correlation (0.674) between leadership structure and performance. The study concluded that governance and leadership structures when handled effectively can yield immense positive results hence leading to improved performance of trade unions. A labour union is an organization by or for the workers to pursue collective workplace goals, wages, benefits and powers. They are intended to represent the collective interests of workers in negotiation with employers over wages, hours of work and working conditions. This study analyzed the adequacy of the legal mandate of labour unions in Uganda and found it adequate but only lacks political will in its implementation and enforcement due to the circumstances under which it was passed. The research also examined the rights and privileges of labour unions. The most hindrance to the enjoyment of these rights and privileges has always been the government's negative attitude towards them as this study explains in the context. The major problems facing labour unions in Uganda are; casualization of labour which leaves workers at the employers' mercy since their terms and conditions of work are not expressly prescribed, unemployment, and insufficient and inadequate facilitated labour officers Due to the decentralization of labour matters, there is need for the establishment of sufficient, well-funded and staffed branches of industrial courts in Uganda, urgency for the grant of the minimum wage that is appropriate to the services rendered to eliminate oppression at workplace and ensure the enforcement of all privileges and rights granted to the workers.